Experimental study between TPU Flex and Silicon Materials Mechanical Properties as an alternatives in development of the CardioVASS Heart Model - Nur Afikah, Khairi @ Rosli; Mohd Azrul Hisham, Mohd Adib; Ming, Mok Chik; Nurul Natasha, Mohd Sukri; Idris, Mat Sahat; Nur Hazreen, Mohd Hasni (2021)
. The development of a heart model for medical training purposes in the current market is still new. The mechanical properties and the selection of materials be-come the main elements in determining the type of materials used. This paper highlighted to study of the mechanical properties between TPU Flex shore 95 A and Room Temperature Vulcanizing (RTV) silicon to determine the suitability of the material for the development of the CardioVASS heart model. Both of the ma-terials were assessed by utilizing the tensile, compression, and hardness test methods to prove the validity of the materials for the CardioVASS heart model. Results suggested that the TPU flex was two times superior to the RTV silicon materials in terms of strength and durability. However, the RTV silicon material was two times elastic rather than the TPU flex material. Both materials can be fabricated as CardioVASS heart model. In future, modification of the mechanical properties of the selected material was expected to form a better and functional heart model